Managing risks in the improved model of rolling mill loading: A case study - Nelli Vladimirovna Syreyshchikova; Danil Yurievich Pimenov; Elena Nikolaevna Yaroslavova; Munish Kumar Gupta; Muhammad Aamir; Khaled Giasin (Journal of Risk and Financial Management, 2021)
This article reflects the main sources of risks for metallurgical enterprises in Russia, presenting the implementation of an innovative approach to increasing the competitiveness of an industrial enterprise, which is a typical representative of large enterprises of the metallurgical industry, based on the development of risk-oriented thinking when loading rolling mills with orders of intersecting assortment according to a new model. To reduce the emerging risks of a new model of the loading process of rolling mills of a metallurgical enterprise, it is proposed to take into account the risks in a complex way, taking into account their interactions with the use of integrated risk management (IRM). Practical development of the implemented approach was carried out by identifying the risks of the new improved loading process and their causes at each stage of the process. Risks were identified by analysis, qualitative and quantitative assessment of the likelihood of risks and the severity of consequences from their implementation with the establishment of events with a high potential hazard. Possible causes of hazardous events have been identified. To reduce the likelihood of unfavorable events, measures have been developed to influence significant risks and their effectiveness has been determined. The development of an innovative approach using risk-based thinking in a previously unexplored field of the application provides competitive advantages for enterprises of the metallurgical industry, increases income by reducing the cost of manufacturing products and production volumes by reducing time costs, achieving an economic efficiency of up to 10 million rubles per year. The practical significance of the dissemination of development results in similar industries is obvious and relevant for metallurgy as a whole.
Keywords: 330; risk management; loading model improvement; mastering; orders with overlapping stock; rolling mill